Development and validation of a UPLC-MS/MS method with volumetric absorptive microsampling to quantitate cyclophosphamide and 4-hydroxycyclophosphamide - Harahap, Yahdiana; Steven, Steven; Suryadi, Herman (Frontiers in Pharmacology, 2022)
Cyclophosphamide (CP) is an anti-cancer alkylating prodrug, metabolized by CYP450 into its active metabolite 4-hydroxycyclophosphamide (4-OHCP). Its therapeutic effectiveness is determined by the 4-OHCP concentration. Several analytical methods in plasma and dried blood spots have been developed to analyze cyclophosphamide and 4-OHCP; however, there are many disadvantages. The objective of this study was to develop and validate the ultraperformance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method by volumetric absorptive microsampling (VAMS) and 4-hydroxycyclophosphamide-d4 (4-OHCP-d4) as an internal standard. VAMS requires small sample volumes, and it is not affected by the hematocrit values; therefore, it is an efficient sampling method. The samples were derivatized with 5 μL semicarbazide hydrochloride (SCZ) and 25 μL of the resulting 4-OHCP-SCZ; 4-OHCP-d4-SCZ derivatives were absorbed by VAMS and extracted by protein precipitation. The optimum conditions were obtained using the Waters Acquity® UPLC BEH C18 (2.1 × 100 mm; 1.7 μm) column; flow rate 0.15 ml/min; mobile phase 0.01% formic acid and methanol; gradient elution mode for 6 min by positive electrospray ionization; and multiple reaction monitoring of m/z 260.7 > 140.0 for CP, 333.7 > 221.0 for 4-OHCP-SCZ, and 337.7 > 225.1 for 4-OHCP-d4-SCZ. The method met the validation requirements set by the FDA. The cyclophosphamide LLOQ value was 5 ng/mL, and the calibration curve range was 5—60,000 ng/ml. Furthermore, the 4-OHCP LLOQ value was 2.5 ng/ml, and the calibration curve range was 2.5—1,000 ng/ml.